Manufacturing Civil Society
XIV, 238 p.
Keywords: Faced with falling social cohesion governments have sought to revitalise society by trying to reconstruct local communities, civil society and citizenship. As a result, civil society is increasingly brought within the realm of public management, subject to accountability and embedded in hierarchies the impact and origins of which this book explores.